ANALYSIS OF FACTORS RELATED TO ANTENATAL CARE VISITS (ANC) IN THE TIME OF THE PANDEMIC COVID-19 IN THE WORKING AREA OF THE MELONG ASIH PUSKESMAS, CIMAHI CITY YEAR 2022 - Nurfatwa, Iis Masruroh; Ambarsari, Wulan Novika; Juaeriah, Ryka; Tang, Li Yoong (jfpublisher, 2024)
Introduction. The pandemic conditions mean that the implementation of Antenatal care (ANC) requires time management, ANC is carried out with limited visits and is carried out more through online telecommunication and studying MCH books. ANC examinations during the pandemic must still be carried out by implementing health protocols. Factors related to ANC visits include family support, support from health workers and knowledge. Pregnancy examinations are carried out according to the 10T examination service standard of care. This research was to determine the analysis of factors related to ANC visits during the Covid-19 pandemic in the Melong Asih Health Center working area, Cimahi City. Methods. This research uses a cross sectional approach . The sampling technique in research is a Non Probability Sampling technique in the form of Accidental Sampling as many as 88 respondents. Data were collected using a family support questionnaire , the role of health workers, knowledge and observation of maternal and child health (KIA) books . Data were analyzed univariately and bivariately using the Chi-Square test. Results and Analysis. Statistical test results were obtained from 3 ANC visit factors There is only 1 factor that has a relationship, namely between family support and ANC visits with a value of p = 0.036 < α = 0.05. Discussions. The results of this research can be used as evaluation or policy material by the community health center to update data on pregnant women in the working area of the Melong Asih Community Health Center, Cimahi City.